Estimação de densidades e aplicação em segmentação de imagens - Zambon, Giovana Marassi [UNESP] (2010)
The aim of this work is to study some of the density estimation tec- niques and to apply to the segmentation of medical images. Medical images are used to help the diagnostic of tumor diseases as well as to plan and deliver treatment. A computer image is an array of values representing colors in some scale. The smallest element of the image to which it is possible to assign a value is called pixel. Segmen- tation is the process of dividing the image in portions through the classi¯cation of each pixel. The simplest way of classi¯cation is by thresholding, given the number of portions and the threshold values. Another method is constructing a histogram of the pixel values and assign a portion to each pike. The threshold is the mean between two pikes. As the histogram does not form a smooth curve it is di±cult to discern between true pikes and random variation. Density estimation methods allow the estimation of a smooth curve. Image data can be considered as mixture of different densities. In this project parametric and nonparametric methods for density estimation will be addressed and some of them are applied to CT image data